Human capital management: a tactical approach in improving employee competence and company competitiveness - Melanny Methasari (Institute of Computer Science (IOCS), 2023)
Human capital is effective and humane management in HR management. This study aims to analyze the impact of human capital management on employee competence and company competitiveness. This descriptive quantitative study with a cross-sectional approach took supervisors and senior staff at PT Aerofood ACS as a sample. Company competitiveness data from scales, checklists and documents, and human capital data are designed using the Likert model, as well as competency data compiled according to the HR Department's checklist. The results of the analysis obtained a value of t = 4.877 with a probability of 0.000 (p <0.01) which proves that there is a very significant increase in the human capital management approach to the competence of supervisors and senior staff. The results of inferential analysis and interpretation of document data show that competitiveness is in the form of a company's ability to strengthen its market position which in quantity is classified as stable, over a period of 2-4 years, is able to maintain a relationship with pro-environmental behavior, increase the number of workers and meet the demands of service user companies workforce at the skill level.